Penerapan Pembuatan Kabel LAN Straight dan Cross sebagai Media Penguatan Kompetensi Jaringan si SMKN 53 Jakarta (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to strengthen students’ networking competencies through the implementation of straight and cross LAN cable assembly training at SMKN 53 Jakarta. The background of this research is based on the need to enhance students’ practical skills in basic computer networking, particularly in understanding cable configurations and applying crimping techniques according to industry standards. Many students experience difficulties in differentiating wiring standards and applying correct crimping procedures, which impacts their readiness for industry practice. This research employed a practical training approach combined with demonstration and hands-on methods. The participants were students of the Computer and Network Engineering program. Data were collected through observation, performance assessment, and competency tests before and after the implementation. The findings indicate a significant improvement in students’ understanding of cable color standards (T568A and T568B), accuracy in assembling straight and cross cables, and testing results using LAN testers. Students demonstrated higher levels of technical accuracy, problem-solving skills, and work discipline after the intervention. The implementation of structured practical activities proved effective as a medium for strengthening networking competencies. The study implies that continuous practice-based learning aligned with industry standards is essential in vocational education to improve students’ technical readiness and employability in the networking field.